Perancangan Sistem Informasi Monitoring Persediaan Bahan Kimia dengan Pendekatan Persediaan Continuous Review (Studi Kasus: Departemen Printing-Dyeing PT Kusumahadi Santosa) - Ikhsan Aditama; Yusuf Priyandari; Wakhid Ahmad Jauhari (Performa: Media Ilmiah Teknik Industri, 2015)
PT Kusumahadi Santosa is a company engaged in manufacturing, the textile industry. One of the major processes that occurs within the company is printing process where types of chemicals that are used are more than 250 different types. However, in conducting the management of chemical inventories, the company still use the manual process which has not been computerized. As a result, there are some problem occurs, such as miscalculation of 5%-30% in the process of recording the amount of chemicals, process of discharging chemicals not recorded, control and planning of chemical inventories is not optimum that will indirectly result in losses company. Therefore, it is necessary to design information system management inventory for controlling chemical inventories. Information system management is designed in the form of web applications and integrated with continuous review inventory model. In addition, the system is equipped with functional and non-functional requirements to fix of the previous system. By adopting the proposed information systems management, the process management of chemicals can be managed more effectively and efficiently. The proposed information system which integrated the system with continuous review inventory model can be adopted by the company for managing the inventories and reducing the inventory cost.